Bioinspired Superhydrophobic Ni–Ti Archwires with Resistance to Bacterial Adhesion and Nickel Ion Release. Issue 7 (25th January 2019) - Liu, Ruoxi; Liu, Xi; Zhou, Jie; Nie, Qiong; Meng, Jingxin; Lin, Jiuxiang; Wang, Shutao
Abstract: Although orthodontic archwires are made from biomedical materials with vast potential for applications worldwide, great challenges, including the adhesion of cariogenic bacteria, the release of nickel ions, and the weakness of mechanical strength, remain and affect their biocompatibility and service life. Herein, a bioinspired superhydrophobic nickel–titanium alloy archwire is reported that displays multifunctional properties of antibacteria adhesion, antinickel release, and corrosion resistance. Compared with commercially purchased archwires, these performances on superhydrophobic archwires can be significantly elevated by varying the contact mode between archwires and the bacterial suspension from surface contact to point contact. Thus, this bioinspired superhydrophobic design has the potential to be applied in other dental devices and provides new ideas for developing novel multifunctional biomaterials. Abstract : Biomedical materials including orthodontic archwires always face great challenges, such as the adhesion of cariogenic bacteria and the release of nickel ion. By varying the archwire‐bacterial suspension contact mode from surface contact to point contact, the bioinspired superhydrophobic nickel‐titanium alloy archwire shows the excellent resistance of bacteria adhesion and nickel ion release.